2024
DOI: 10.1001/jamapsychiatry.2023.4294
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Deficit/Hyperactivity Disorder Medications and Long-Term Risk of Cardiovascular Diseases

Le Zhang,
Lin Li,
Pontus Andell
et al.

Abstract: ImportanceUse of attention-deficit/hyperactivity disorder (ADHD) medications has increased substantially over the past decades. However, the potential risk of cardiovascular disease (CVD) associated with long-term ADHD medication use remains unclear.ObjectiveTo assess the association between long-term use of ADHD medication and the risk of CVD.Design, Setting, and ParticipantsThis case-control study included individuals in Sweden aged 6 to 64 years who received an incident diagnosis of ADHD or ADHD medication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 48 publications
0
13
0
1
Order By: Relevance
“…Pharmacoepidemiological studies have also shown reduced risks of negative outcomes, including injuries, traffic collisions, and criminality, which would be expected to decrease the mortality rate . However, there are concerns regarding the cardiovascular safety of ADHD medications, especially following long-term use, which could increase the mortality rate …”
Section: Introductionmentioning
confidence: 99%
“…Pharmacoepidemiological studies have also shown reduced risks of negative outcomes, including injuries, traffic collisions, and criminality, which would be expected to decrease the mortality rate . However, there are concerns regarding the cardiovascular safety of ADHD medications, especially following long-term use, which could increase the mortality rate …”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear whether and to what extent this increase in blood pressure is associated with an increased risk of cardiovascular conditions, as existing evidence is mixed. Some prospective and retrospective cohort studies have reported an increased risk of cardiovascular events in individuals receiving methylphenidate treatment . In contrast, other retrospective, population-based cohort studies did not find any association between methylphenidate use and cardiovascular events …”
Section: Introductionmentioning
confidence: 99%
“…Another reason that clinicians may not initiate treatment is the concern about adverse effects and discomfort in managing them. This concern may intensify considering recent data that long-term use of stimulant medications may increase rates of hypertension or atherosclerosis, a risk that stabilizes over time. However, as demonstrated by this study, such risk should be weighed against the risk of premature mortality that appears to be mitigated with ADHD treatment.…”
mentioning
confidence: 99%